Systemic Therapy in Advanced Cutaneous Squamous Cell Carcinoma (CSCC): The Roswell Park Experience and a Review of the Literature. (December 2016) - Jarkowski, Anthony; Hare, Ryan; Loud, Peter; Skitzki, Joseph J.; Kane, John M.; May, Kilian S.; Zeitouni, Nathalie C.; Nestico, Jill; Vona, Karen L.; Groman, Adrienne; Khushalani, Nikhil I.
Abstract : Objectives: Treatment of locally advanced unresectable or metastatic cutaneous squamous cell carcinoma (mCSCC) is suboptimal with a paucity of robust data on systemic therapy. This retrospective study aimed to evaluate the efficacy and outcomes of patients with locally advanced unresectable or mCSCC treated with systemic therapy. Methods: Records of patients with CSCC treated with systemic therapy from January 2001 to January 2011 were reviewed. Response was assessed using WHO criteria. Descriptive results were assessed using Wilcoxon rank-sum test for ordinal responses and Pearson χ 2 test for categorical responses. Survival was calculated by the Kaplan-Meier method. Results: Of 28 patients identified, 25 patients (M:F=18:7), median age 66 years (range, 39 to 85 y), had the required data for final analysis. Partial response was 44% and stable disease (SD) was 24%. The median progression-free survival (PFS) and overall survival (OS) were 5.5 months (2.3, 13.2) and 10.9 months (5.3, 21.3) respectively; 3-year OS was 22%. Patients with WHO response had improved PFS (20.8 mo; 4.4, NR) and OS (37.5 mo; 10.3, NR) compared with patients with SD/PD (PFS 2.7 mo; OS 5.9 mo). Use of platinum-based therapy significantly improved PFS and OS, whereas taxanes and cetuximab had no impact in this small cohort. There was no difference in PFS or OS with multiagent versus single-agent therapy. Conclusions: Platinum-based therapy remains as one of the standard options in advanced CSCC management. Agents to improve response rates are needed and future trials should address the use of novel targeted and new chemotherapy combinations in CSCC.